PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASI - Dedy Wahyudi; Onsardi Onsardi; Yeriza Nur Permata Utama (Yayasan Insani Mandiri Santani, 2025)
The purpose of this study is to analyze how individual characteristics, job characteristics and compensation affect Employee Organizational Commitment (PT. Indomarco Adi Prima Bengkulu Branch Stock Point Salebar). The sampling method is using the total sampling method. This study was conducted quantitatively descriptively and involved 44 respondents. Observation, interviews, and questionnaires were used to collect data. Instrument testing, classical assumption testing, simple linear regression, coefficient of determination (R2), and hypothesis testing (t test) and f test were used to analyze the data. This shows that individual characteristics, job characteristics and compensation have a positive and significant effect on Employee Organizational Commitment (PT. Indomarco Adi Prima Bengkulu Branch Stock Point Salebar). Keywords: Individual Characteristics, Job Characteristics, Compensation and Employee Organizational Commitment